MOTIVATIONAL INTERVIEWING: TECHNIQUES FOR INCREASING STUDENT ACADEMIC INDEPENDENCE IN THESIS COMPLETION - Utami, Ferisa Prasetyaning; Rosyidah , Hani’; Sari , Permata (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
Insufficient independence leads to reduced encouragement and individual drive when it comes to accomplishing goals and resolving issues. This is particularly crucial for students who bear the sole responsibility of completing their thesis. Hence, they must possess the autonomy to tackle and solve it. The objective of this study was to examine the efficacy of motivational interviewing as a technique to enhance academic independence among final-semester students who are working on their thesis. The research employed an experimental approach, utilizing a design known as non-equivalent control group design. The participants of the study consisted of both an experimental group (N=7) and a control group (N=7). The intervention involved five group counselling sessions. The results of the hypothesis test, conducted using the Mann Whitney U test, revealed that the Asymp.sig (2-tailed) value was 0.002, which is less than 0.05. Therefore, it can be concluded that the motivational interviewing technique effectively enhances academic independence. Furthermore, the findings indicate that the increase in independence is accompanied by the emergence of intrinsic motivation, which serves as the primary driving force for students to complete their thesis.